Peningkatan kesadaran lingkungan berbasis lanskap kejepangan bagi masyarakat Desa Wisata Lerep, Kabupaten Semarang - Althaf Gauhar Auliawan; Lilis Lamsehat Panjaitan; Muhammad Zaki Fadhlurrahman; Dimas Ananta Tarigan (Nur Science Institute, 2026)
This community service activity was driven by the need to increase environmental awareness in the Lerep tourist village, Semarang Regency, Central Java. Given the extraordinary natural potential of the Lerep tourist village, environmental awareness still needs to be maintained amidst environmental issues and climate change. The goal of this activity is to increase awareness and knowledge of the Lerep tourist village community about environmental conservation, as well as provide practical skills in sustainable environmental management, particularly in maintaining the natural beauty of the Japanese landscape. The methods used in this training include lectures, interactive discussions involving the community, stakeholders, and students, and product creation. The results of this community service activity are increased environmental awareness in the community, the implementation of Japanese culture-based environmental awareness training, and the production of environmental awareness education brochures as a sustainable campaign medium, which is expected to contribute significantly to increasing tourist visits that have a positive impact on the environment and the local economy.